1992
DOI: 10.1073/pnas.89.20.9504
|View full text |Cite
|
Sign up to set email alerts
|

Retroviral analysis of cardiac morphogenesis: discontinuous formation of coronary vessels.

Abstract: Cellular progenitors of the coronary vasculature are believed to enter the chicken heart during epicardlal morphogenesis between stages 17 and 27 (days 3-5) of egg incubation. To trace cells which give rise to the coronary arteries in vivo, we applied retroviral cell tagging procedures and analyzed clonal populations of vascular smooth muscle, endothelium, and connective tissue in the hearts of post-hatch chickens. Our data provide direct proof that (t) vascular smooth muscle progenitors begin to enter the hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
280
0
2

Year Published

1996
1996
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 357 publications
(291 citation statements)
references
References 21 publications
(34 reference statements)
9
280
0
2
Order By: Relevance
“…The differentiation of proepicardial/epicardial cells into CoSMCs was first reported in a series of studies based on a retroviral in vivo labeling (Mikawa and Fischman, 1992;Mikawa and Gourdie, 1996). Subsequently, a number of studies using quail-to-chick proepicardial transplantations confirmed and expanded these observations (Fig.…”
Section: Epdcs and Cosmcsmentioning
confidence: 85%
See 1 more Smart Citation
“…The differentiation of proepicardial/epicardial cells into CoSMCs was first reported in a series of studies based on a retroviral in vivo labeling (Mikawa and Fischman, 1992;Mikawa and Gourdie, 1996). Subsequently, a number of studies using quail-to-chick proepicardial transplantations confirmed and expanded these observations (Fig.…”
Section: Epdcs and Cosmcsmentioning
confidence: 85%
“…In a series of elegant retroviral labeling studies, Mikawa and colleagues (Mikawa and Fischman, 1992;Mikawa and Gourdie, 1996) clearly showed that the coronary system does not derive from the myocardium or from the endocardium, but that instead the proepicardium was the source of coronary endothelium. The retroviral studies did not, however, provide any data on the specific origin of the coronary progenitors found within the proepicardium.…”
Section: The Fate Of the Epdc Epdcs And Coronary Endotheliummentioning
confidence: 99%
“…Morphologic and experimental studies point to a transitory structure, the proepicardium (PE), a grape-like cluster of mesothelial cells derived from the pericardial serosa that extends to and migrates over the myocardial surface during the looping, tubular stage of heart development (Manasek, 1969;Ho and Shimada, 1978;Viragh and Challice, 1981;Komiyama et al, 1987;Kuhn and Liebherr, 1988;Fransen and Lemanski, 1990;Manner, 1992;Mikawa and Fischman, 1992;Viragh et al, 1993;Munoz-Chapuli et al, 1994;Mikawa and Gourdie, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Common to all vertebrate species, once the epicardial sheet has formed, some its cells undergo an epithelial-mesenchymal transformation that gives rise to connective tissue cells of the subepicardium and myocardium, and the angiogenic precursors of the coronary vessels (Mikawa and Fischman, 1992;Dettman et al, 1998;Vrancken Peeters et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The first step in establishing a coronary vasculature involves the migration of angioblasts from the subepicardium into the myocardium, their differentiation into endothelial cells, and their assembly to form vascular tubes (Mikawa and Fischman, 1992;Poelmann et al, 1993;Rongish et al, 1994;Viragh et al, 1993). This process is termed vasculogenesis and also consists of fusion of the vascular tubes (a process reviewed by Drake and Little, 1999).…”
Section: Introductionmentioning
confidence: 99%